Functional Outcome of Mesenchymal Stem Cells Vs. Hyaluronic Acid in Knee Osteoarthritis Kellgren-Lawrence Grade I-III At 6-and 12-Months Follow-Up: A Meta-Analysis - I Gusti Ngurah Wien Aryana; Febyan; Shianita Limena (Universitas Airlangga, 2023)
Background: Osteoarthritis (OA) is a degenerative synovial joint disease with progressive pain and deformity. Stem cell therapy, especially mesenchymal stem cells (MSCs), has revolutionized the treatment of knee OA. However, clinical evidence for MSCs in the treatment of knee OA is insufficient. The primary objective of this research is to offer substantiation and recommendations for advancing and utilizing MSC therapy in clinical settings, in contrast to the use of hyaluronic acid (HA) as the standard control group.Methods: This study was a meta-analysis conducted through a search for relevant scientific reports in PubMed, Embase, and Google Scholar, using some keywords such as